2017
DOI: 10.1158/0008-5472.can-16-2345
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Dynamics in B-cell Lymphoma: A Longitudinal Prospective Study of Plasma Samples Up to 25 Years before Diagnosis

Abstract: The B-cell activation markers CXCL13, sCD23, sCD27, and sCD30 are associated with future lymphoma risk. However, a lack of information about the individual dynamics of markerdisease association hampers interpretation. In this study, we identified 170 individuals who had donated two prediagnostic blood samples before B-cell lymphoma diagnosis, along with 170 matched cancer-free controls from the Northern Sweden Health and Disease Study. Lymphoma risk associations were investigated by subtype and marker levels m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
6
13
0
Order By: Relevance
“…Therefore any reported mediating effect for the marker itself should be interpreted as a proxy of the underlying biologic milieu that is captured by circulating levels of those molecules that is partly mediating the alleged associations. We observed strong associations between sCD23, sCD27, sCD30, and CXCL13 in blood samples collected up to 19 years before diagnosis and risk of BCL development, consistent with previous studies [8][9][10][11][12]28,29 . The associations between sCD23 levels and development of BCL subtype were the most stable associations in this study, particularly for CLL, which was significant even more than 9 years before BCL diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore any reported mediating effect for the marker itself should be interpreted as a proxy of the underlying biologic milieu that is captured by circulating levels of those molecules that is partly mediating the alleged associations. We observed strong associations between sCD23, sCD27, sCD30, and CXCL13 in blood samples collected up to 19 years before diagnosis and risk of BCL development, consistent with previous studies [8][9][10][11][12]28,29 . The associations between sCD23 levels and development of BCL subtype were the most stable associations in this study, particularly for CLL, which was significant even more than 9 years before BCL diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study by Späth et al . nested within the Northern Swedish Health and Disease Study cohort is, to our knowledge, the only other besides our own to use repeated samples, with samples collected an average of 8 years apart . In comparisons between repeated samples, a rise in serum levels of sCD27 and sCD30 was observed for cases, particularly those diagnosed within 3 years of the second sample collection, consistent with a disease‐induced effect.…”
Section: Discussionmentioning
confidence: 73%
“…During the past few years a number of studies reported on the ability of various biomarkers measured in the blood of apparently healthy subjects to predict the risk of future diagnosis of CLL [ 12 16 ]. These predictive biomarkers concern cell surface markers and mitochondrial DNA copy number and provide limited insight into cellular processes that precede clinical disease.…”
Section: Introductionmentioning
confidence: 99%